(untitled) (Homiletic, 2025)
Preaching has traditionally been understood as verbal proclamation within religious settings. However, Accompanying Preaching introduces a novel pastoral-theological framework that expands this concept by integrating presence, relationality, and solidarity with the lived experiences of individuals. This paper explores the practices of Accompanying Preaching as a lived experience, particularly in contexts of social and pastoral challenges. It draws from real life experiences in catechetical missions, educational settings, and moments of crisis, illustrating how preaching is fundamentally an act of being with others rather than just speaking to them. By formalizing this approach, Accompanying Preaching is proposed as a theological and pastoral framework that may serve as a guide for preachers, catechists, and pastoral workers in their mission. Grounding this framework in theological reflection and practical experience, this study contributes to the broader discourse on mission and pastoral engagement.